2016
DOI: 10.1377/hlthaff.2015.1087
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Interventions To Improve Influenza Vaccine Uptake Among Health Care Workers

Abstract: Despite official recommendations for health care workers to receive the influenza vaccine, uptake remains low. This systematic review of randomized controlled trials was conducted to understand the evidence about interventions to improve influenza vaccine uptake among health care workers. We identified twelve randomized controlled trials that, collectively, assessed six major categories of interventions involving 193,924 health care workers in high-income countries. The categories were educational materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 43 publications
5
42
0
2
Order By: Relevance
“…Since risk perception of vaccination rates is higher in pandemics periods, Sevencan et al found the rates 36.4% whereas Ormen et al detected the rates up to 40.0% [13,14]. The reason for lower rates of vaccination in similar studies conducted worldwide is similar to the reasons detected in our country [15,16,17]. The most common reasons for rejection of the vaccination include being afraid of side effects of the vaccine, not believing the effectiveness of the vaccine and not considering the vaccine safe [18].…”
Section: Discussionsupporting
confidence: 72%
“…Since risk perception of vaccination rates is higher in pandemics periods, Sevencan et al found the rates 36.4% whereas Ormen et al detected the rates up to 40.0% [13,14]. The reason for lower rates of vaccination in similar studies conducted worldwide is similar to the reasons detected in our country [15,16,17]. The most common reasons for rejection of the vaccination include being afraid of side effects of the vaccine, not believing the effectiveness of the vaccine and not considering the vaccine safe [18].…”
Section: Discussionsupporting
confidence: 72%
“…These results were similar to results from recent review articles on interventions to increase influenza vaccination coverage among HCP, which reported that vaccination uptake increases with an increasing number of intervention program components in hospital and non-hospital settings. 24,27,35 …”
Section: Discussionmentioning
confidence: 99%
“…However, there has been little qualitative research into these phenomena; thus, the relationship between these factors and why they arise remains unclear. Previous attempts to improve vaccine uptake have had limited success; however, studies which include a combination of interventions (focused around education, convenience, and leadership) appear slightly more effective ( Rashid et al, 2016 )—suggesting that some ambiguous complexities remain in current understanding.…”
Section: Introductionmentioning
confidence: 99%